2017
DOI: 10.1161/strokeaha.116.014250
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Open-Label, Phase 1/2a Study to Determine the Maximum Tolerated Dose of Intraventricular Sustained Release Nimodipine for Subarachnoid Hemorrhage (NEWTON [Nimodipine Microparticles to Enhance Recovery While Reducing Toxicity After Subarachnoid Hemorrhage])

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In the last 15 years, monitorization of SDs in patients after stroke and brain trauma at intensive care units has been established in multiple centers under the framework of Co-Operative Studies on Brain Injury Depolarizations (COSBID). More than 500 patients have been monitored in multiple centers in various countries, and multiple trials are currently in process, such as DISCHARGE-1, Invasive and Non-Invasive Monitoring of Spreading Depolarization by Electrocorticography in Trauma and Stroke (INSPECT), NEWTON trial (Nimodipine microparticles to Enhance recovery While reducing TOxicity after subarachNoid hemorrhage) and MHS trials [158]. Although the monitorization of the actual patients pointed out some pathological pathways, there have also been some limitations of human trials of SDs.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, monitorization of SDs in patients after stroke and brain trauma at intensive care units has been established in multiple centers under the framework of Co-Operative Studies on Brain Injury Depolarizations (COSBID). More than 500 patients have been monitored in multiple centers in various countries, and multiple trials are currently in process, such as DISCHARGE-1, Invasive and Non-Invasive Monitoring of Spreading Depolarization by Electrocorticography in Trauma and Stroke (INSPECT), NEWTON trial (Nimodipine microparticles to Enhance recovery While reducing TOxicity after subarachNoid hemorrhage) and MHS trials [158]. Although the monitorization of the actual patients pointed out some pathological pathways, there have also been some limitations of human trials of SDs.…”
Section: Introductionmentioning
confidence: 99%
“…Nimodipine, an oral calcium channel blocker first introduced in 1985, was the drug typically used to treat SAH and was suggested to effectively prevent neuroischaemic events after SAH . A recent randomized trial showed that the intrathecal application of nimodipine not only reduces DCI, but also improves clinical outcome and that this approach is safe . Other vasodilators, such as fasudil, clazosentan and nicardipine, have also been shown to have some potential value for the treatment of vasoconstriction, although they may induce systemic hypotension and cerebral perfusion pressure …”
Section: The Pathophysiology Of Sahmentioning
confidence: 99%
“…Those include transluminal balloon angioplasty and intra-arterial drug administration; typical agents include verapamil, papaverine, nimodipine, and milrinone. Current areas of study include nitric oxide donors, endothelin-1 antagonists, low-dose heparin, and intrathecal agents; the NEWTON2 trial is currently underway to evaluate intraventricular sustained-release nimodipine for SAH [ 38 ]. Opportunities exist for developing sustained-release spasmolytics, as well as intra-arterial neuroprotectants that could be injected during the time of standard intra-arterial treatments for vasospasm.…”
Section: Conference Proceedings—october 4–5 2017mentioning
confidence: 99%